PDTM-02. TARGETING THE RB PATHWAY IN MEDULLOBLASTOMA. (11th November 2019) - Jonchere, Barbara; Stripay, Jennifer; Pribnow, Allison; Zindy, Frederique; Min, Jaeki; Freeman, Burgess; Shelat, Anang; Rankovic, Zoran; Roussel, Martine
Abstract: Medulloblastoma (MB), the most common malignant pediatric brain tumor, is classified into four major molecularly and histopathologically distinct subgroups, among which MYC-driven Group 3 MBs confer a poor prognosis. The Cyclin D/CDK4/CDK6/RB pathway is frequently deregulated in MB leading to uncontrolled cell proliferation, but tumors express an intact RB protein ( Northcott et al., Nature, 2017 ). Therefore, CDK4/6 inhibitor drugs offer a possible therapeutic approach to treat MBs. Because single agent therapy ultimately leads to drug resistance, we initiated in vitro combination drug screens to identify drug classes potentiating CDK4/6 inhibitors. We used Group 3 MB patient-derived orthotopic xenografts (PDOXs), a human cell line (HDMB03), and freshly dissociated tumor cells propagated only in the mouse brain. The drug screen included 90 compounds comprising targeted and cytotoxic drugs that are FDA approved or under active clinical investigation. Using a bioluminescence-based assay that measures ATP consumption (CellTiter-Glo) to evaluate the number of viable cells, these 90 compounds were screened in combination with a fixed concentration of ribociclib, one of the three FDA approved CDK4/6 inhibitors. The primary screen, carried out in HDMB03 cells, revealed several drugs with additive or synergistic potential when combined with ribociclib, including BET inhibitors, MEK inhibitors, PI3K/mTOR inhibitors and gemcitabine. We are currently evaluating the combination of brain penetrant compounds in Group 3 MB PDOXs. The identification of potent drug combinations should provide new therapeutic options for the treatment of Group 3 MB, one of the most difficult to treat.